MiR-564: A potential regulator of vascular smooth muscle cells and therapeutic target for aortic dissection. (September 2022) - Li, Min; Yang, Yanyan; Zong, Jinbao; Wang, Zhibin; Jiang, Shaoyan; Fu, Xiuxiu; He, Xiangqin; Li, Xiaoxin; Xue, Qianqian; Wang, Jian-Xun; Yu, Tao
Abstract: Background: Aortic dissection (AD) is a lethal cardiac disorder and one of the most concerning cardiovascular diseases (CVDs). Increasing evidence indicates that human aortic vascular smooth muscle cells (VSMCs) play a crucial role in the pathogenesis of AD, especially related to phenotypic transformation. And notablely, the development of AD is also accompanied by inflammation. Methods: By using quantitative real-time PCR and fluorescence in situ hybridization (FISH), we detected the expression levels of miR-564 in vitro and in vivo. The effects of miR-564 proliferation and migration were investigated in VSMCs. The downstream targets of miR-564 were found by bioinformatics analyse, and verified in the regulation on VSMCs. An AD murine model was constructed and clinical evaluation was performed to explore the critical roles of miR-564 in vivo. At the same time, the level of inflammation was detected using quantitative real-time PCR and immunofluorescence. Results: Overexpression of miR-564 inhibited cell proliferation and migration, as well as phenotype switch, with or without platelet-derived growth factor BB (PDGF-BB) treatment, whereas downregulation of miR-564 led to opposite results. Mechanistically, miR-564 directly interacted with the target genes proto-oncogene (SKI) and neurogranin (NRGN) to regulate the biological functions of VSMCs. In particular, animal experiments demonstrated that miR-564 can alleviate the progression of AD mainly through mediating phenotypic swithing and inflammation which was consistent with clinical evaluation. Conclusions: Our study identified miR-564 as a significant molecule that attenuates AD progression by inhibiting inflammation and VSMCs proliferation, migration and phenotypic transformation, suggesting that it may be a potential therapeutic target for AD. Graphical abstract: MiR-564 regulates the biological function of VSMC via targeting SKI and NRGN leading to mediating the onset and progression of aortic dissection. Unlabelled Image Highlights: Low miR-564 levels were found in patient arteries. miR-564 suppresses cell proliferation, migration and phenotype switch of VSMCs. miR-564 directly interacts with SKI and NRGN to regulate VSMC functions. miR-564 alleviated AD progression in a mouse model which could be considered as a potential therapeutic target for AD.